ALS Mimics due to Affection of the Cervical Spine: From Common Compressive Myelopathy to Rare CSF Epidural Collection - Storti, Benedetta (Case Rep Neurol, 2021)
Amyotrophic lateral sclerosis (ALS) is a clinically heterogeneous disease, with chameleon presentations and several mimics. Considering the poor prognosis of ALS, their precise and timely identification is pivotal. Affection of the cervical spine represents one potential source of ALS mimics that should never be missed, since it is potentially treatable. We hereby present 5 cases initially diagnosed as ALS but eventually found to have different kinds of cervical spine affection, from a common compressive myelopathy to a rare space-occupying cystic fluid collection.